Soil moisture and soil organic carbon coupled effects in apple orchards on the Loess Plateau, China - Lei Han; Guowei Nan; Xinyu He; Jinghui Wang; Jirong Zhao; Xiangqian Zhang (Scientific Reports, 2024)
Abstract A large number of economic forests, especially apple orchards (AOs) in the Loess Plateau region of China, have been planted to develop the local economy and increase the income of farmers. The two main constraints preventing AOs on the Loess Plateau from developing sustainably and producing a high and steady yield are soil moisture content (SMC) and soil organic carbon (SOC). Nevertheless, little is currently known about the contributions of roots to these changes in the soil profile and the temporal modes of the SMC-SOC coupled effects. In our research, we analyzed the dynamic changes in SMC and SOC in AOs of various years in northern Shaanxi Province, as well as the coupled relationship between the two, and attempted to describe the function of roots in these changes. Research have shown: (1) As the age of the AOs increased, the SMC continued to decline throughout the 0–500 cm profile, especially at depths of 100–500 cm. SMC depletion mainly occurred in AOs aged 20 years (30.02%/year) and 30 years (31.18%/year). (2) Compared with abandoned land (AL), all the AOs except for the 6-year-old AO showed a carbon sequestration effect, and the carbon sequestration effect increased with age. The carbon sequestration rate of the 12-year-old AO was the highest and then decreased with age. Both surface and deeper soils showed better carbon sequestration, with a large amount of SOC being sequestered in deeper soil layers (> 100 cm). (3) The coupled effects of SMC and SOC varied with age and depth. The SMC in the deeper layers was significantly negatively correlated with SOC. Root dry weight density (RDWD) was significantly negatively correlated with SMC and significantly positively correlated with SOC. Path analysis suggested that SMC directly affects SOC at different soil depths, and regulates SOC by affecting RDWD, but these effects are significantly different at different depths. Therefore, we propose that management of AO should focus on the moisture deficit and carbon sequestration capabilities of deeper soils to ensure the sustainability of water use in AOs and the stability of agricultural carbon sequestration on the Loess Plateau.